Multidimensional mass spectrometry characterization of isomeric biodegradable polyesters. Issue 6 (December 2017) - Sallam, Sahar; Luo, Yuanyuan; Becker, Matthew L; Wesdemiotis, Chrys
The biodegradable polyester copolymer poly(propylene fumarate) (PPF) is increasingly utilized in bone tissue engineering studies due to its suitability as inert cross-linkable scaffold material. The well-defined poly(propylene fumarate) oligomers needed for this purpose are synthesized by post-polymerization isomerization of poly(propylene maleate), which is prepared by ring opening polymerization of maleic anhydride and propylene oxide. In this study, multidimensional mass spectrometry methodologies, interfacing matrix-assisted laser desorption ionization and electrospray ionization with mass analysis, tandem mass spectrometry fragmentation and/or ion mobility mass spectrometry, have been employed to characterize the composition, end groups, chain connectivity and isomeric purity of the isomeric copolyesters poly(propylene maleate)and poly(propylene fumarate). It is demonstrated that the polymerization catalyst is incorporated into the polymer chain (as the initiating chain end) and that the poly(propylene maleate) to poly(propylene fumarate) isomerization using an amine base proceeds with quantitative yield. Hydrolytic degradation is shown not to alter the double bond geometry of the poly(propylene fumarate) or poly(propylene maleate) chains.